(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
More Pancit Canton wants to penetrate the market, meet the demand of the customers, and satisfy the potential customers. More Pancit Canton will serve high-quality services to easily reach the customers and vice versa. Hence, the researchers conducted this study. First, due to the seeking of feasible strategy for descriptive research design, secondary data from books and the Internet were used. Second, the financial statement was analyzed concerning the areas if it is profitable. The business used a survey questionnaire to obtain the valid primary data of 50 respondents and guided with SWOT analysis. The gathered data from the respondents showed that the potential customers love the business and are in favor of ages 18 and above. Second, the secondary data from books and the Internet were used to get more information such as from foreign and local related studies, history, and the updated sales forecast of the product. Third, the financial statement’s general purpose is to provide information about the result of the operation, that is, the return of investment (ROI). The ROI is 13.63% in 2019, 8.90% in 2020, 13.63% in 2021, 19.08% in 2022, and 25.35% in 2023. This study recommended the following. The owners need to continuously improve what the business offers and its promos to meet people’s satisfaction, which changes over time. This is a good strategy to catch every customer’s attention and loyalty. The researchers need to be aware of the latest technology and be able to compete with other companies.